The impact of rewards on police officers performance: The case of Kondoa district - Mwengu, Greyson I (Mzumbe University, 2024)
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Human Resource Management (MSc.HRM) of Mzumbe University